2019
DOI: 10.21608/jhiph.2019.63793
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study for Socioeconomic Inequalities in Health among Jordanian Adolescents

Abstract: Background: Socioeconomic inequalities play an important role in health. Although studies report less inequalities in adolescent health compared to other age groups, there may be differences in their health behavior and mental health. Objective(s): This cross-sectional pilot study aimed to analyze these associations. Methods: Using a sample of students (n = 112, aged 13-18 years) data were collected from public and private schools in Irbid governorate, Jordan, November, 2018. Measurements included socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…For example, male students reported they did not have enough food at home more frequently than female students. Likewise, males reported eating fewer fruit and vegetables daily compared to their female counterparts; this finding is consistent with previous Jordanian studies [ 30 , 33 ]. In terms of an unhealthy diet, male students were more likely to report drinking carbonated soft drinks and eating more fast food than females.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, male students reported they did not have enough food at home more frequently than female students. Likewise, males reported eating fewer fruit and vegetables daily compared to their female counterparts; this finding is consistent with previous Jordanian studies [ 30 , 33 ]. In terms of an unhealthy diet, male students were more likely to report drinking carbonated soft drinks and eating more fast food than females.…”
Section: Discussionsupporting
confidence: 92%
“…Among the few Jordanian studies that have been conducted, Obeisat and Gharaibeh [ 29 ] reported that boys and adolescents with a higher family income were more likely to engage in physical activity [ 29 ]. Alshammari and Piko [ 30 ] found that fruit and vegetable consumption was associated with higher parental education, while fast food consumption was associated with higher family affluence. In terms of smoking, initiators of smoking were more likely to be males and those with less educated parents [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation